Fishing for Fish and for Jaminyjarti in Northern Aboriginal Australia. Issue 1 (March 2014) - Toussaint, Sandy
Abstract Socio‐cultural and ecological literature about Australian Indigenous groups reveal that fishing is a vital part of everyday life for many groups who have customary and recreational fresh and salt‐water affiliations. This vitality exists and has meaning for families and communities in the Kimberley's Fitzroy Valley region of Northern Aboriginal Australia. Less well known, however, is the central part that fishing plays in jaminyjarti, a ritual that relies on close kin regularly catching, cooking and sharing fish for bereaved family members during the 'sorry business' time that emerges after the death of a loved one. What becomes evident is that while fishing is undoubtedly intertwined in the everydayness and sociality of life, it is also central to comforting the bereaved during and after the grieving process that accompanies death.